â PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWANâ (Study Pada Dinas Tenaga Kerja dan Transmigrasi Provinsi Jawa Tengah) - Wiwik Sulyani, 14.05.51.0061; Suko Priyono, Bambang (Students Journal of Economic and Management, 2018)
This study aims to in order to understand the the influence of leadership that we are doing , much of his best work discipline and fuel compensation , in coordinated with partial or unwillingly as these pay rises on performance tens of thousands of workers. The data used in the research is the primary data was , with the questionnaire as absence of research , who after that it is processed with an amount of spss ( statistical product saw a private economic analyst said ) version 20 .Percent of the population in this research was an employee at the office of jakarta manpower and transmigration city of central java province , that the others were twice 341 workers bitter .The technique of over the withdrawal of funds by smeru within the was used in the study random sampling by using the method what is the formula slovin , so that research a significant proportion of respondents there were a total of 100 respondents in the present study .An instrument the analysis used is linear regression of multiple. The results of the study indicate that there has the influence of there had been a positive leadership that we are doing in welfare between these pay rises on performance tens of thousands of workers .There have been instances of the influence of there had been a positive much of his best work in welfare between discipline these pay rises on performance tens of thousands of workers .There have been instances of the influence of there had been a positive significant.Keyword: leadership, work discipline, compensation and of employee performance.